ILLOCUTIONARY FORCE OF SLANG WORDS IN "RAMPAGE" 2018 MOVIE - Ratri, Ayu; Ena, Ouda Teda; Bram, Barli (BASIS (Bahasa dan Sastra Inggris), 2022)
Slang words can contain particular meanings that cannot be interpreted directly. To know and understand the meaning behind the utterances, EFL learners can employ illocutionary force by analyzing the native speakers' daily communication of slang words. Therefore, this qualitative research aimed to explore the types of slang words and the illocutionary force behind the utterances in the Rampage movie. The data were collected from the movie transcript and analyzed using document analysis to explore the types of slang words and the illocutionary force. The analysis results revealed that all types of slang words were discovered in the movie, and the most used type was imitative, which occurred 14 times. The illocutionary force that underlined the characters implementing the slang words was to show that the speakers have higher status than the interlocutor, understand what they need to do in certain situations, ask other people to do something, want to show their psychological state, and they want to give a promise. The results of this study would enrich EFL learners' knowledge of slang words in particular and their vocabulary items in general.